An interdisciplinary framework for using archaeology, history and collective action to enhance India’s agricultural resilience and sustainability - Green, A. S.; Dixit, S.; Garg, K. K.; Sandya, N. R.; Singh, G.; Vatta, K.; Whitbread, Anthony M.; Jones, M. K.; Singh, R.N.; Petrie, C.A (IOP Publishing, 2020)
South Asia has a deep history of agriculture that includes a range of past farming systems in different climatic zones. Many of these farming systems were resilient to changes in climate and sustainable over long periods of time. India’s present agricultural systems are facing serious challenges, as they have become increasingly reliant on the unsustainable extraction of groundwater for irrigation. This paper outlines an interdisciplinary framework for drawing on patterns from the past to guide interventions in the present. It compares past and present strategies for water management and use in semi-arid and temperate Punjab with equatorial Telangana. Structural differences in water use in these two regions suggest that a range of interventions should be adopted to expand the overall availability of surface water for agricultural systems in India, in combination with empowering local communities to create their own water management rules. Active interventions focus on the efficient use of water supplies, and increasing surface water availability through renovation of collective ponds and reservoirs. We argue that this conceptual framework has significant potential for guiding agronomic and economic interventions in the future.